Seismic effects of loess slopes using physical modeling and numerical simulation - Wujian, Yan; Xinxin, Tian; Zhijian, Wu; Ping, Wang; Lin, Kang (Frontiers in Earth Science, 2023)
A large shaking-table test of a loess slope with a geometric similarity ratio of 1:25 was established as a prototype model of the loess landslide in Yongguang Village, which occurred during the 2013 Minxian–Zhangxian M6.6 earthquake. Combined with finite-element–numerical-simulation software, the dynamic response characteristics of the loess slope were compared and analyzed under the action of the same Minxian horizontal seismic wave characteristics. The results show that the seismic waves observed in the model test and numerical simulation clearly exhibit non-linear amplification effects along the slope surface and in the loess vertical direction, reaching a maximum value at the top of the slope. The ground-motion acceleration waveforms observed in the model test and numerical simulation at each observation point of the slope were similar, and the horizontal peak ground acceleration (PGA) obtained from the numerical simulation at these locations was larger than that of the slope top. The horizontal aSimulated-max/aModel-max values ranged from 1.5 to 2.2 and the vertical aSimulated-max/aModel-max values were more discrete in the range of 0.5–2.7, while the horizontal and vertical-PGA-amplification factors at the slope surface were similar. The Fourier amplitude and main horizontal frequencies were mainly distributed between 0.1 and 12 Hz. The Fourier spectrum observed in the model test was approximately 0.5 Hz, while the main frequency of the vertical Fourier spectrum was approximately 4 Hz. Additionally, the main frequency of the horizontal and vertical Fourier spectra observed in the numerical simulation was approximately 2 and 1.2 Hz, respectively.